PENDIDIKAN AL-QUR’AN SEBAGAI MODAL PEMBENTUKAN KARAKTER SISWA DI MADRASAH DINIYAH - Haris, Abd (Universitas Islam Madura, 2017)
The more the spirit of study of the Qur'an is increasing, so the spirit of studying the Qur'an is never lost, For that, learning knowledge about the Qur'an should be given to all students, ranging from the level of childhood to they mature later. On the other hand, character education that is currently being promoted and developed by the government is an education that prioritizes the behavior of good morality. The education of this character emerges and rises to the surface is a reaction to the advancement of pedagogig (education) naturalistic and instrumentalism. al-Qur'an that in essence already covers the whole aspects of life, including also the education, so that can be interpreted by studying the Qur'an means the same as improving the character of each child itself. The phenomenon in Madrasah Diniyah in his learning process emphasizes more on religious teaching sessions, as well as the education of the Qur'an, and as the pattern of association of students, that they are in daily life more prioritizes the manners that is already one of the characteristics of has in character education . For that, at a glance the authors assume that character education is an application of education of the Qur'an that they have learned so far.